IMPLEMENTASI LEAN DALAM STRATEGI PEMASARAN DI RUMAH SAKIT GIGI DAN MULUT: TINJAUAN LITERATUR - Prastiwi, Arini Cyndwiana; Ayuningtyas, Dumilah (UI Scholars Hub, 2023)
Hospitals as health services must make strategies in developing marketing activities so that they get a good response from the community. Oral and Dental Hospital (RSGM) is a health service that provides dental and oral health services in the form of prevention, treatment and recovery as well as providing emergency, outpatient, and inpatient services. The growing number of RSGM has forced health service management to plan the right marketing strategy to increase and maintain interest in patient visits. In addition, RSGM must also pay attention to service quality and cost efficiency. The benefits of lean in marketing can improve service quality and productivity by determining useful value and eliminating waste so that it can maximize its potential and marketing can be in accordance with the target market. This study was conducted descriptively, and the search results will be associated with Lean in the discussion as a method to help identify the right marketing strategy based on available resources. The benefits of lean in marketing strategy are that it can help identify the right marketing mix using several types of tools, for example fishbone diagrams, and reduce unnecessary waste in RSGM marketing efforts Dental and oral hospital, Marketing strategy, Lean